Predictive Value of Direct Disk Diffusion Testing from Positive Blood Cultures for Detection of Antimicrobial Nonsusceptibility - Tammy Ting-Yan Wong; Chung-Ho Lee; Hester Wing-Sum Luk; Cindy Wing-Sze Tse; Pak-Leung Ho (Microorganisms, 2025)
Antibiotic resistance poses a significant global threat, particularly in the context of bloodstream infections. Early antimicrobial susceptibility testing plays a crucial role in guiding clinicians to optimize treatment and enhance patient outcomes. Direct disk diffusion testing (dDDT), utilizing positive blood culture broth as an inoculum, provides results one day earlier than the standard method using bacterial colonies. This retrospective study evaluated the ability of dDDT to predict nonsusceptibility to commonly used antibiotics. From January 2021 to December 2023, a total of 1473 blood cultures positive for a single pathogen (Enterobacterales, Pseudomonas aeruginosa, Staphylococcus aureus, β-hemolytic streptococci, or Enterococcus spp.) were examined. The results of dDDT were compared against the standard disk diffusion method as the reference standard. A total of 9754 organism–antibiotic pairs were analyzed. The positive predictive values were more than 98% for clinically significant resistant phenotypes, including ceftriaxone, ceftazidime, cefepime, and meropenem nonsusceptibility in Enterobacterales, ceftazidime and meropenem nonsusceptibility in P. aeruginosa, and cefoxitin resistance in S. aureus. Overall, sensitivities exceeded 98% for the majority of organism–antibiotic pairs, with specificities ranging from 88.4% to 100%. Categorical agreement was high at 97.9%, ranging from 88.8% to 100% across organism groups. The overall rates of major error and very major error were very low, at 0.2% and 0.04%, respectively, and ranged from 0% to 1.5% and 0% to 0.04%, respectively, across organism groups. In conclusion, dDDT is a reliable and expedient method for detecting antibiotic nonsusceptibility, making it a valuable tool for the timely management of bloodstream infections caused by resistant organisms.